Conflict and Sensitivity Analysis of Articulated Vehicle Lateral Stability Based on Single-Track Model. (31st December 2021) - Peng, Dengzhi; Fang, Kekui; Kuang, Jianjie; Hassan, Mohamed A.; Tan, Gangfeng
Abstract : Lateral stability is quite essential for the vehicle. For the vehicle with an articulated steering system, the vehicle load and steering system performance is quite different from the passenger car with the Ackman steering system. To investigate the influence of the tire characteristics and vehicle parameters on lateral stability, a single-track dynamic model is established based on the vehicle dynamic theory. The accuracy of the built model is validated by the field test result. The investigated parameters include the tire cornering stiffness, vehicle load, wheelbase, and speed. Based on the snaking steering maneuver, the lateral stability criteria including the yaw rate, vehicle sideslip angle, tire sideslip angle, and lateral force are calculated and compared. The sensitivity analysis of the tire and vehicle parameters on the lateral stability indicators is initiated. The results demonstrated that the parameters that aﬀect the lateral vehicle stability the most are the load on the rear part and the tire cornering stiffness. The ﬁndings also lay a foundation for the optimization of the vehicle's lateral stability.